Holy piracy: Kopimism, the sacralisation of information, and the legitimating power of religion - Walker, Seth M. (Culture and religion, 2018)
Kopimism is a new religious movement predicated on, and revolving around, the assertion and belief that information is inherently sacred and needs to be copied and shared. Adherents to this Swedish-born religious movement have persisted in small pockets of devout communities around the world for almost a decade. This paper outlines a rudimentary and general sketch of the Kopimist worldview, its basic aims and its place within the contemporary religious landscape. In the latter part of this analysis, particular attention is given to the movement's claim that it is not simply a sacralisation of political ideals - pirate politics, in particular - but that it maintains a distinct worldview and ethical system based on the notion that information - the foundation of everything - is itself divine. "Religion" as a legitimating categorical force and the sociocultural conditions that engender new religious movements are also considered alongside the movement's history and development.